2000
DOI: 10.1038/emm.2000.22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allyl sulfur compounds and garlic extract on the expression of Bcl-2, Bax, and p53 in non small cell lung cancer cell lines

Abstract: Allyl sulfur compounds play a major role in the chemoprevention against carcinogenesis. The present study compared the antiproliferative effects of diallyl sulfide (DAS), diallyl disulfide (DADS) and garlic extract on p53-wild type H460 and p53-null type H1299 non small cell lung cancer cells (NSCLC). The DAS and DADS treatment of both H460 and H1299 cells resulted in the highest numbers of cells in apoptotic state as measured by acridine orange staining, however, garlic extract treatment did not induce any si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(94 citation statements)
references
References 22 publications
6
83
3
Order By: Relevance
“…Moreover, garlic oil presented a prominent ability to induce cell apoptosis using staining with Annexin V-FITC/PI, confirming that the underling mechanism of anti-proliferation was mainly mediated by an induction of apoptosis, also proved by our further investigation of TEM and FCM. The above results were similar to the earlier report that garlic oil is effective in the reduction of anti-proliferative gene and modulation of apoptosis-associated cellular proteins in non small cell lung cancer cells (Hong et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, garlic oil presented a prominent ability to induce cell apoptosis using staining with Annexin V-FITC/PI, confirming that the underling mechanism of anti-proliferation was mainly mediated by an induction of apoptosis, also proved by our further investigation of TEM and FCM. The above results were similar to the earlier report that garlic oil is effective in the reduction of anti-proliferative gene and modulation of apoptosis-associated cellular proteins in non small cell lung cancer cells (Hong et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Using other cell lines, Al 2 S and Al 2 S 2 , in contrast to Al 2 S 3 , seem to cause only a slight decrease in the expression of Bcl-2 and a slight increase in Bax expression, a reflection of the fact that Al 2 S and Al 2 S 2 are only weak inducers of apoptosis (16). This notion has been confirmed in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have demonstrated the efficacy of garlic compounds as antitumorigenic agents. For example, DADS inhibits the in vitro growth of colon, lung, breast and gastric cancer cell lines, and leukemia cell lines [8][9][10][11][12], indicating that DADS may be a useful therapeutic tool in the prevention of environmentally induced cancers. We previously reported that DADS induced G2/M arrest and inhibited growth of MGC803 cells.…”
Section: Introductionmentioning
confidence: 99%